Incidence of incomplete excision of basal cell carcinoma and associated factors at two tertiary hospitals - Hoogendyk, Charles August (University of the Witwatersrand, Johannesburg, 2023)
Introduction: Basal Cell Carcinomas (BCC) account for the majority of skin cancers in South Africa. They have low mortality but can cause significant morbidity primarily through local destruction, therefore recurrence should be mitigated. Surgery is the preferred treatment for BCC. The excision margin is determined firstly by oncological safety and then preservation of normal tissues. Therefore, a wider or narrower margin increase the risk for aesthetic complications and recurrence, respectively. However, the optimal surgical excision margin size remains unclear and guidelines established based on lesion size and histological aggression are inconsistent. This may be because incomplete excision has a more complex relation with other associated factors. Aim: The aim of this study was to examine the rate of incomplete excision (involved margin) of BCC at tertiary Hospitals in South Africa, and to assess the influence from associated factors, such as age, sex, histological type, size, site, and lesion occurrence (primary; re-excision; recurrence). Method: This was a retrospective quantitative observational study with chart reviews, performed at the Plastic Surgery Department at the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) and Chris Hani Baragwanath Academic Hospital (CHBAH). Patients who underwent BCC excision from January 2016 to December 2020 were screened and biopsies were collected. The normality of continuous data (age and biopsy size) was tested with Shapiro-Wilks test. The standard descriptive statistics and interquartile ranges (IQR) were reported. Involved excisional margins associations with continuous and categorical variables were tested using the Mann-Whitney U test, and Chi-squared test, respectively. Results: he cohort consisted of 226 patients who underwent a total of 461 biopsies. The median age was 65.3 years, there were predominantly male (56.0%) patients, from CHBAH (81.0%). Baseline associated factors of largest biopsies (n=226) and smallest (n=91) biopsies of the cohort were examined overall. Margin was involved at excision on 16.8% (38/226) of largest samples and 23.1% (21/91) of smallest biopsies. The commonest site was the Head and Neck region, with 146 (64.6%) in the largest biopsies and 61 (67.0%) amongst smallest biopsies. The commonest subtype was nodular which was 38.9% (88/262) and 40.6% (37/91) amongst the largest and smallest, respectively. On assessment of the diameter and the involved excisional margin, there was a significant association for smallest biopsy (p<0.001). On cross-tabulation, involved excisional margin for larger biopsies was significantly associated with head and neck biopsies (p<0.001) and aggressive lesions (p=0.004). In smallest biopsies lesions, involved excisional margin was also associated with head and neck sites (p=0.009) and primary occurrence (p<0.001), and smallest biopsies in the head and neck region was associated with aggressive type lesions (p=0.003). In the latter group, indolent type lesions were associated with primary biopsies (p=0.001). Conclusion: In this population the associated factors for margin involvement on excision are head and neck site, aggressive type, and non-primary lesions. For best patient outcomes, and the prevention of BCC recurrence, we recommend that these factors are considered when deciding on excision margin size.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in Plastic Surgery, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023
Keywords: Margin involvement; Excision; Basal Cell Carcinomas (BCC); Oncological safety; Preservation of normal tissues.; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education